Strategi Optimalisasi Kemampuan Pertolongan Pertama Manajemen Epistaksis dan Syncope dengan Pendekatan Doflet pada Remaja - Nian Afrian Nuari; Efa Nur Aini; Kirani Firstyana Ramadhani; Kristian Hadi Saputra; Laella Chabibah; Lailatul Qodariyah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Epistaxis or commonly called nosebleed is bleeding in the nasal vestibule, nasal cavity, or nasopharynx that is acute. Fainting is an emergency situation where someone experiences a life-threatening condition that requires immediate assistance. This usually occurs in school students who are performing ceremonies, or outdoor activities. The purpose of this community service is to improve first aid skills in epistaxis and syncope management with the DOFLET method in adolescents. The partners of this community service are 21 adolescents at SMK X. This service method uses the DOFLET method (demonstration and leaflet) by providing training to demonstrate/demonstrate how to handle using available tools directly to improve first aid skills in epistaxis and syncope management in adolescents at SMK X. Based on the results obtained, the results before being given first aid training for epistaxis and syncope management were mostly in the sufficient category and after being given training, most were in the good category. The results of the statistical analysis also showed the influence of the strategy for optimizing first aid for epistaxis and syncope management with the ability to provide first aid in adolescents. The strategy for optimizing first aid education for epistaxis and syncope is expected to help students understand how to provide first aid correctly, as well as increase students' insight into preventing epistaxis and syncope.